Education and Climate Change: Discovering Strategies for Individual and Collective Action - Samantha Govender; Mncedisi C. Maphalala; Dumisani W. Mncube; Arorisoe Sibanda; Azwidohwi P. Kutame; Cleopatra Luthuli; Hlengiwe R. Mhlongo; Kofi N. Mpuangnan; Lindiwe C. Mthethwa; Lyn Kok; Nokuthula P. Xulu; Petrus J. Kok; et al. (AOSIS, 2025)
This scholarly book explores education's vital yet underemphasised role in addressing climate change, positioning it as both a powerful tool for climate action and a sector directly impacted by environmental challenges. Challenging traditional, fact-based educational models, the book advocates for a transformative framework that integrates social-emotional learning, interdisciplinary collaboration, and action-oriented teaching. Through empirical research, theoretical insights, and real-world case studies – such as the Keep it Cool – Climate Change Education (KIC-CCE) initiative in South Africa – it illustrates how education can drive awareness, empower communities, support green employment, and foster resilience, particularly among marginalised populations. Aligning with the United Nations'Sustainable Development Goals 4 (quality education) and 13 (climate action), the book highlights the importance of teacher preparedness, gender equality, and community engagement. Rich in academic rigour and practical relevance, it first offers scholars, but also policymakers and practitioners, a forward-thinking perspective on integrating climate change education into curricula and broader educational systems.